Isolation and Community Resettlement: a Labrador Example - Richling, Barnett (Culture)

(untitled) (Canadian Anthropology Society / Société Canadienne d’Anthropologie (CASCA), formerly/anciennement Canadian Ethnology Society / Société Canadienne d’Ethnologie, 1985)
The social conception of isolation in hinterland communities is seen as a manifestation of economic and political dependency, and not merely as a function of physical remoteness. This paper examines how isolation influences local decision-making about population resettlement as a strategy of community development. Based on data from a small Labrador village, the study considers how isolation has been experienced over time, and how it affects the identification of developmental priorities and objectives among local factions.